1998
DOI: 10.1101/gad.12.22.3499
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β regulates cyclin D1 proteolysis and subcellular localization

Abstract: The activities of cyclin D-dependent kinases serve to integrate extracellular signaling during G 1 phase with the cell-cycle engine that regulates DNA replication and mitosis. Induction of D-type cyclins and their assembly into holoenzyme complexes depend on mitogen stimulation. Conversely, the fact that D-type cyclins are labile proteins guarantees that the subunit pool shrinks rapidly when cells are deprived of mitogens. Phosphorylation of cyclin D1 on a single threonine residue near the carboxyl terminus (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

101
1,817
7
20

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,968 publications
(1,945 citation statements)
references
References 71 publications
101
1,817
7
20
Order By: Relevance
“…The di erence in p21 staining between the two populations was highly signi®cant (P50.009). This result further provides support for the hypothesis that D1 + D3 + p21 + cancers are defective in the machinery responsible for the degradation of these proteins rather than in other proteins a ecting cyclins D1 and D3 degradation speci®cally such as GSK-3b (Diehl et al, 1998). Further, as *60% of breast cancers have been shown to overexpress p21 but only *30% of these cancers overexpress p53, other p53 independent mechanism leading to p21 overexpression must exist (Rey et al, 1998).…”
Section: Skp2 Associates With Cyclin D3supporting
confidence: 59%
“…The di erence in p21 staining between the two populations was highly signi®cant (P50.009). This result further provides support for the hypothesis that D1 + D3 + p21 + cancers are defective in the machinery responsible for the degradation of these proteins rather than in other proteins a ecting cyclins D1 and D3 degradation speci®cally such as GSK-3b (Diehl et al, 1998). Further, as *60% of breast cancers have been shown to overexpress p21 but only *30% of these cancers overexpress p53, other p53 independent mechanism leading to p21 overexpression must exist (Rey et al, 1998).…”
Section: Skp2 Associates With Cyclin D3supporting
confidence: 59%
“…The stability of cyclin D1 protein plays a major role in the regulation of its expression. Phosphorylation of the cyclin on Thr 286 results in the rapid proteasomal degradation of the protein (Diehl et al, 1998). Whether or not metformin may lead to the phosphorylation of cyclin D1 remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both mTOR and GSK3b are major downstream targets of Pten/PI3K/AKT signals in eliciting their functions in cell cycle progression, cell growth and proliferation (Mita et al, 2003). Moreover, it has been shown that high levels of pAKT and pGSK3b are frequently associated with increased nuclear accumulation of cyclin D1 (Diehl et al, 1998;Gotoh et al, 2003). To investigate this, we next performed immunohistochemical staining using an antibody to cyclin D1.…”
Section: Aurora-a Induces Mammary Tumor Formation X Wang Et Almentioning
confidence: 99%